Teaching STEM Entrepreneurship With Societal Significance: Building on the Small Business Innovation Research Program. (2nd July 2022) - Bandera, Cesar
Undergraduate students are aware of problems with societal significance, but few have tacit knowledge on how to address them through entrepreneurship or how to research the multidisciplinary technical, financial, and regulatory requirements. This paper describes a one-semester entrepreneurship course that teaches undergraduate students how to identify societally significant opportunities for STEM-based innovations, and how to de-risk associated business models. This course differs from traditional entrepreneurship education in three ways. First, it builds upon the federal Small Business Innovation Research (SBIR) program ("America's Seed Fund"). Second, students learn to navigate the multidisciplinary strategic decisions that often accompany business models developed for societally impactful opportunities. Third, by becoming intimately familiar with proposal writing and submission protocols, those students willing to commit to entrepreneurship, or intrapreneurship if in the job market, have better chances of raising significant funds (>1 M) through the SBIR program than from equity investors or commercial banks. The experiential nature of the course promotes students' ability to discover tacit opportunities, whereas learning SBIR protocols promotes students' ability to discover codified opportunities. The paper presents the pedagogical concepts, learning objectives, and evaluation criteria of this novel course.